AN ALTERNATIVE METHOD FOR POINT POSITIONING IN THE FORESTED AREAS - Pirti, Atinc; Tunalioglu, Nursu; Ocalan, Taylan; Hosbas, R. Gursel (CROATIAN FORESTRY SOC, 2016)
Global Navigation Satellite Systems (GNSS) consist of satellite technologies such as GPS, GLONASS, Bei Dou and Galileo. These technologies have effectively been used in many application areas. GNSS Continuously Operating Reference Stations (CORS) have also been applied successfully in many areas of forested industry Typical applications include fire prevention and control, harvesting operations insect infestation, boundary determination, and aerial spraying. Forest and natural resource applications can be achieved efficiently employing GNSS/CORS data collection technologies. However, there are limiting factors in the environment, such as the forest canopy, which has adverse effects on the reception of GNSS signals. In terms of saving time, Point Positioning with GNSS/CORS in forested areas is a significant challenge in the acquisition of highly accurate coordinates of points. The time for integer carrier-phase ambiguity solution takes approximately one-hour or more for point positioning under forested areas with GNSS/CORS. In this study, an alternative method for providing point coordinates under a forested area is proposed. This method gives the positioning results with centimeter level accuracy and nearly 15 minutes are required to provide the new point location in the forested area. The method proposed may also be of practical use in indoor applications with desired accuracy at cm level, which is reached in a short observation time. In this study, we conducted fieldwork to achieve coordinates of the point in a forested area with GNSS/CORS system and supplementary measurements by establishing two control points observed by GNSS/CORS located at the border of the forested area. The result shows that a satisfactory solution for forested area is reached at cm level (approximate to +/- 6 cm),in a short observation time.
Keywords: GNSS; CORS; VRS; Accuracy; Forested Areas; GPS; ENVIRONMENT; Forestry